SISTEM INFORMASI GEOGRAFIS PEMETAAN KAWASAN RAWAN BANJIR DAN JALUR EVAKUASI DI KABUPATEN MALAKA - Seran, Aprilianus; Belalawe, Benyamin Jago (Lembaga Pengembangan Kinerja Dosen, 2025)
Malaka Regency in East Nusa Tenggara Province is prone to flooding, especially during the rainy season due to the overflowing Benenain River. Flooding in this area has a serious impact on people's lives, such as disruption of transportation, economic activities, and increased health risks. This research aims to map flood-prone areas and determine optimal evacuation routes by utilizing Geographic Information Systems (GIS). The methods used are overlay and network analysis with the support of ArcGIS software. The data obtained is integrated into a web-based information system using open source technologies such as PHP, MySQL, and XAMPP, and equipped with login and CRUD features. System testing using the White Box method shows that all functions run well. The results show that GIS is able to provide an accurate spatial picture and assist in evacuation planning more systematically. For future development, the system is recommended to have a more interactive display and more detailed maps up to the village level to support more effective disaster mitigation.